Chitosan / polydopamine / copper sulfide composite hydrogel as well as preparation method and application thereof

By compounding chitosan, polydopamine and copper sulfide, a multifunctional hydrogel is constructed, which solves the shortcomings of traditional hemostatic materials in hemostatic speed, antibacterial properties and mechanical strength, and achieves the effects of rapid hemostasis, antibacterial and photothermal response, making it suitable for complex first aid scenarios.

CN120617600APending Publication Date: 2025-09-12CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510825063.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-19
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Traditional hemostatic materials have deficiencies in hemostasis speed, antibacterial properties, mechanical strength and biocompatibility, and are difficult to meet the needs in complex bleeding environments, especially in deep wounds, irregular wounds or large-area bleeding.

Method used

By combining chitosan, polydopamine and copper sulfide, a multifunctional hydrogel is constructed. The hemostatic properties of chitosan, the adhesion of polydopamine and the photothermal effect of copper sulfide are utilized to form a composite hydrogel material with rapid hemostasis, antibacterial, photothermal response and good mechanical properties.

Benefits of technology

It achieves rapid hemostasis, antibacterial, photothermal response and good mechanical properties. It is suitable for various scenarios such as surface trauma, deep tissue and organ bleeding. It has excellent injectability and adaptability, low immunogenicity and biocompatibility, and can achieve precise treatment through near-infrared light regulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120617600A_ABST
    Figure CN120617600A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and particularly discloses chitosan / polydopamine / copper sulfide composite hydrogel as well as a preparation method and application thereof. According to the hydrogel, through the synergistic effect of the chitosan, the polydopamine and the copper sulfide nanoparticles, a multifunctional composite system with rapid hemostasis, photo-thermal antibiosis, shape adaptability and biocompatibility is constructed. Chitosan promotes platelet aggregation and thrombin generation, polydopamine enhances adhesiveness and simulates an extracellular matrix, copper sulphide endows photo-thermal response ability, and heat energy can be efficiently converted to kill bacteria under near-infrared light irradiation. The preparation method comprises the following steps: firstly preparing polydopamine, then synthesizing copper sulfide nanoparticles, and then obtaining the composite hydrogel. The hydrogel has excellent injectability, self-repairability and conductivity, the hemolysis rate is smaller than 5%, the blood coagulation index is remarkably increased, the hydrogel is suitable for treatment of body surface wounds, deep tissue bleeding and infectious wounds, and a low-cost and efficient solution is provided for clinical hemostasis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials, and in particular relates to a chitosan / polydopamine / copper sulfide composite hydrogel and a preparation method and application thereof. Background Art

[0002] In the medical field, the demand for hemostatic materials is extremely widespread, especially in clinical scenarios such as surgery and trauma emergency treatment. Rapid and effective hemostasis is crucial for emergency treatment and reducing complications. However, while traditional hemostatic materials (such as gelatin sponges and cellulose dressings) can be effective in certain scenarios, they generally have many shortcomings, such as slow hemostasis, insufficient antibacterial properties, and easy adhesion to wounds. These defects make it difficult to meet the needs of complex bleeding environments, especially in deep wounds, irregular wounds, or large-area bleeding.

[0003] Photothermal antibacterial materials have the property of absorbing near-infrared (NIR) lasers and converting them into thermal energy. They have been widely studied in many fields such as biomedicine. However, they mostly rely on precious metals (such as gold and silver nanoparticles) and have problems such as high cost and limited biocompatibility.

[0004] Chitosan (CS), as a natural biopolymer material, can promote platelet aggregation and thrombin generation due to its good biocompatibility, antibacterial and hemostatic properties, thereby accelerating the hemostasis process. However, simple chitosan hydrogel has significant deficiencies in hemostatic performance. It mainly relies on amino electrostatic adsorption to promote platelet aggregation, but cannot directly activate coagulation factors. In severe bleeding, the coagulation rate is slow, and the platelet plugs formed are easily detached by blood flow impact, resulting in poor hemostasis reliability. At the same time, it has low mechanical strength and weak adhesion, and is easy to fall off in a moist wound environment. The structure is prone to collapse after absorbing water, affecting the sustained hemostasis effect.

[0005] Hydrogels, as soft materials with three-dimensional network structures, have shown promising application in hemostasis due to their excellent biocompatibility and water absorption properties, absorbing blood moisture and concentrating coagulation components. However, single-component hydrogels often struggle to simultaneously meet multiple functional requirements, such as rapid hemostasis, antibacterial properties, and mechanical strength. Summary of the Invention

[0006] The purpose of this invention is to provide a chitosan / polydopamine / copper sulfide composite hydrogel, designed to address the shortcomings of traditional hemostatic materials in terms of hemostatic speed, antibacterial properties, mechanical strength, and biocompatibility. By organically combining the hemostatic properties of chitosan (CS), the adhesive and bioactive properties of polydopamine (PDA), and the photothermal effect of copper sulfide (CuS), a multifunctional composite hydrogel material with rapid hemostasis, antibacterial properties, photothermal response, and excellent mechanical properties was constructed to meet the hemostatic needs of complex emergency scenarios.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] (1) Preparation of polydopamine (PDA)

[0009] Dopamine hydrochloride (DA) was dissolved in a 0.1-0.2 M NaOH aqueous solution at pH 9-11 and allowed to oxidatively autopolymerize at room temperature for 24-48 hours with stirring, forming a dark brown homogeneous solution. The reaction solution was placed in a dialysis bag (molecular weight cut-off 3500 Da) and dialyzed against deionized water for 48 hours to remove unreacted monomers and salts. The precipitate was collected by centrifugation and freeze-dried to produce PDA powder.

[0010] The concentration of the reaction solution of dopamine hydrochloride in the NaOH aqueous solution is 2-5 mg / mL, the centrifugal speed is 8000-12000 rpm, and the freeze-drying time is 24-48 hours.

[0011] (2) Preparation of copper sulfide nanoparticles (CuS NDs) by hydrothermal method

[0012] Copper chloride dihydrate (CuCl2·2H2O) and polyvinylpyrrolidone (PVP, molecular weight 4000) were mixed in a mass ratio of 7:20 (21 mg:60 mg) and dissolved in 5 mL of deionized water. The mixture was magnetically stirred at room temperature until a light blue, transparent solution formed. Sodium sulfide nonahydrate (Na2S·9H2O, 30 mg) was then added, and the solution quickly turned dark brown. Stirring was continued for 5 minutes to ensure uniform mixing. The reaction system was transferred to an oil bath and maintained at 80-90°C for 15-45 minutes. After the reaction, the solution was cooled to room temperature. The solution was dark green.

[0013] Post-processing involves a gradient purification process: the reaction mixture is first placed in a dialysis bag (molecular weight cut-off 3500 Da) and dialyzed against deionized water to remove small molecule impurities. High-speed centrifugation is then performed, and the supernatant is filtered through a 0.22 μm filter membrane to obtain a uniformly sized CuS NDs dispersion. The product is stable when stored at 4°C.

[0014] The dialysis time is 24-48h, and the centrifugal speed is 8000-12000rpm.

[0015] After dialysis purification, the CuS NDs dispersion was freeze-dried (pre-freezing at -80°C for 4 h and drying at 1000 hPa in vacuum for 24-48 h) to obtain a solid powder to ensure the stability of the photothermal material and the accuracy of the subsequent composite hydrogel preparation.

[0016] (3) The steps of preparing the composite hydrogel are as follows:

[0017] 1) Preparation of polydopamine stock solution: Dissolve PDA powder in 1% glacial acetic acid solution and sonicate to obtain a 2-5 mg / mL PDA solution.

[0018] 2) Chitosan-polydopamine pre-assembly: dissolving chitosan in the PDA solution of step (1) and stirring to form a homogeneous system;

[0019] The amount of chitosan used is 40% of the total mass of chitosan.

[0020] 3) Multi-component cross-linking: CuCl2·2H2O and CuS NDs were added to the homogeneous system in step (2) and 2+ -Catechol coordination bond and chitosan amino ion cross-linking form a composite system;

[0021] The mass ratio of CuCl2·2H2O to CuS NDs is 1:2.5-10.

[0022] 4) Chemical cross-linking strengthening: 60 μL of 1-2% glutaraldehyde solution was added dropwise to initiate the Schiff base reaction and construct a three-dimensional network gel precursor;

[0023] The dropping rate of the glutaraldehyde solution is 1-2 drops / second, and the stirring time is 30-60 minutes.

[0024] 5) Gelation control: Add chitosan powder and stir until a composite hydrogel is formed. The stirring and gelation time is 5-10 minutes.

[0025] The total mass ratio of the added chitosan, polydopamine and copper sulfide nanoparticles is 1:0.04-0.1:0.01-0.04.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention constructs a multifunctional hydrogel hemostatic material by compounding chitosan (CS), polydopamine (PDA) and copper sulfide nanoparticles (CuS NDs), and realizes the integrated functions of rapid hemostasis and photothermal antibacterial through the synergistic effect of the three. Chitosan promotes platelet aggregation and thrombin generation to accelerate blood coagulation, and the high adhesion of polydopamine enables the hydrogel to fit tightly to the wound surface, sealing the wound and preventing leakage, and shortening the in vitro coagulation time. Copper sulfide nanoparticles trigger local temperature rise (50-60°C) under near-infrared light (1060nm), and the copper ions (Cu 2+ ) formed coordination bonds with the catechol groups in polydopamine (PDA) and simultaneously produced ionic crosslinking with the amino groups of chitosan (CS), thus constructing a three-dimensional network structure of the composite hydrogel. 2+The introduction of CuS did not destroy the photothermal conversion performance of copper sulfide (CuS). Instead, it stabilized the composite system, allowing the photothermal effect to act more evenly on the wound and improving the antibacterial efficiency (inhibition rate > 99%).

[0028] (2) The composite hydrogel of the present invention has excellent injectability and adaptability, and is suitable for various scenarios such as surface trauma, deep tissue and organ bleeding. It forms a three-dimensional network through dynamic hydrogen bonding and chemical cross-linking, with a storage modulus (G') ≥ 300Pa. It can be injection molded and conform to irregular wounds. The self-healing performance (strain cycle recovery rate > 90%) ensures that the material maintains its integrity under mechanical stress and avoids shedding due to movement.

[0029] (3) The composite hydrogel of the present invention has low immunogenicity, biodegradability and biocompatibility, does not require secondary removal after use, and is suitable for in vivo hemostatic treatment.

[0030] (4) The composite hydrogel of the present invention has photothermal responsiveness and can achieve precise treatment through near-infrared light regulation; it breaks through the limitations of single functional materials and integrates hemostatic, antibacterial, and antioxidant functions, significantly improving the hemostatic effect on wounds.

[0031] (5) The preparation process of the present invention is simple and low-cost, which solves the limitation of traditional photothermal materials that rely on precious metals (such as gold and silver nanoparticles). BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The left side shows dopamine (DA) and the right side shows the actual picture of the polydopamine (PDA) solution of Example 1;

[0033] Figure 2 1 is the ultraviolet absorption spectrum of dopamine (DA) and polydopamine (PDA) in Example 1;

[0034] Figure 3 Schematic diagram of the synthesis steps of the photothermal material CuS in Example 1;

[0035] Figure 4 This is a photo of the gelation of chitosan / polydopamine composite hydrogel in comparative example 1;

[0036] Figure 5 This is a photo of the gelation of the chitosan / polydopamine / copper sulfide composite hydrogel in Example 1;

[0037] Figure 6 This is a graph showing the rheological amplitude data of the chitosan / polydopamine / copper sulfide composite hydrogel in Example 1;

[0038] Figure 7 This is a graph showing the rheological frequency data of the chitosan / polydopamine / copper sulfide composite hydrogel in Example 1;

[0039] Figure 8This is the rheological self-repairing data diagram of chitosan / polydopamine / copper sulfide composite hydrogel in Example 1;

[0040] Figure 9 This is the rheological shear diagram of the chitosan / polydopamine / copper sulfide composite hydrogel in Example 1;

[0041] Figure 10 Example 1: Chitosan / polydopamine / copper sulfide composite hydrogel rheological self-healing physical diagram;

[0042] Figure 11 This is a photo of the chitosan / polydopamine / copper sulfide composite hydrogel recovering after compression in Example 1;

[0043] Figure 12 Compression data of chitosan / polydopamine / copper sulfide composite hydrogels with different CuS contents;

[0044] Figure 13 This is a photo of the injectable chitosan / polydopamine / copper sulfide composite hydrogel of Example 1;

[0045] Figure 14 This is a photo of the shape-adaptive filling of the chitosan / polydopamine / copper sulfide composite hydrogel in Example 1;

[0046] Figure 15 This is a graph showing the viscometer measurement data of the chitosan / polydopamine / copper sulfide composite hydrogel in Example 1;

[0047] Figure 16 This is a photo of the chitosan / polydopamine / copper sulfide composite hydrogel dynamically adapting to finger motion in Example 1;

[0048] Figure 17 This is a photo of the adhesion of the chitosan / polydopamine / copper sulfide composite hydrogel under external force in Example 1;

[0049] Figure 18 This is a photo of the chitosan / polydopamine / copper sulfide composite hydrogel adhered to different materials in Example 1 (from top to bottom, adhered to a rubber bottle stopper, a polymer PP bottle cap, a polymer PE centrifuge tube, and a glass slide);

[0050] Figure 19 This is a photo of chitosan / polydopamine / copper sulfide composite hydrogel adhered to glass bottles of different weights in Example 1;

[0051] Figure 20 This is a photo showing the adhesion of the chitosan / polydopamine / copper sulfide composite hydrogel to the heart, liver, spleen, lung, and kidney of mice in Example 1;

[0052] Figure 21 This is a photo showing the adhesion of the chitosan / polydopamine / copper sulfide composite hydrogel to damaged mouse heart, liver, spleen, lung, and kidney in Example 1;

[0053] Figure 22 This is the conductivity data diagram of CuS and PDA materials in Example 1;

[0054] Figure 23 The conductivity data of chitosan / polydopamine / copper sulfide composite hydrogels with different CuS contents;

[0055] Figure 24 This is the data graph of the anti-oxidative DPPH of chitosan / polydopamine / copper sulfide composite hydrogel in Example 1;

[0056] Figure 25 The results of the DPPH antioxidant experiment of chitosan / polydopamine / copper sulfide composite hydrogel in Example 1 are shown (from top to bottom: Control, CS / PDA, CS / PDA / CuS);

[0057] Figure 26 The temperature rise curve of chitosan / polydopamine / copper sulfide composite hydrogel with 0.5 mg / mL CuS NDs under laser irradiation at different powers;

[0058] Figure 27 The temperature rise curve of chitosan / polydopamine / copper sulfide composite hydrogel with 0.75 mg / mL CuS NDs under laser irradiation at different powers;

[0059] Figure 28 The temperature rise curve of chitosan / polydopamine / copper sulfide composite hydrogel with 1 mg / mL CuS NDs under laser irradiation at different powers;

[0060] Figure 29 This is the temperature rise curve of 1 mg / mL CuS NDs under repeated cycles of 1060 nm, 0.9 W laser irradiation;

[0061] Figure 30 This is the temperature rise curve of chitosan / polydopamine / copper sulfide composite hydrogel with 1 mg / mL CuS NDs under repeated cycles of 1060 nm and 0.9 W laser irradiation;

[0062] Figure 31 The figure shows the effect of chitosan / polydopamine / copper sulfide composite hydrogel at different incubation times on the survival rate of S. aureus (agar plate counting method);

[0063] Figure 32 The effect of chitosan / polydopamine / copper sulfide composite hydrogel on the survival rate of S. aureus after incubation for 10 minutes (bar graph);

[0064] Figure 33This is the effect of chitosan / polydopamine / copper sulfide composite hydrogel on the survival rate of S. aureus after incubation for 20 minutes (bar graph);

[0065] Figure 34 The figure shows the effect of chitosan / polydopamine / copper sulfide composite hydrogel at different incubation times on the survival rate of E. coli (agar plate counting method);

[0066] Figure 35 This is the effect of chitosan / polydopamine / copper sulfide composite hydrogel on the survival rate of E. coli after incubation for 10 minutes (bar graph);

[0067] Figure 36 This is the effect of chitosan / polydopamine / copper sulfide composite hydrogel on the survival rate of E. coli after incubation for 10 minutes (bar graph);

[0068] Figure 37 The data graph and experimental results of chitosan / polydopamine / copper sulfide composite hydrogel destroying the formed S. aureus biofilm;

[0069] Figure 38 The data graph and experimental results of chitosan / polydopamine / copper sulfide composite hydrogel destroying the formed E. coli biofilm;

[0070] Figure 39 This is the data diagram of the hemolysis experiment of chitosan / polydopamine / copper sulfide composite hydrogel;

[0071] Figure 40 Schematic diagram of the chitosan / polydopamine / copper sulfide composite hydrogel coagulation experiment steps;

[0072] Figure 41 This is the data diagram of chitosan / polydopamine / copper sulfide composite hydrogel coagulation experiment;

[0073] Figure 42 Schematic diagram of chitosan / polydopamine / copper sulfide composite hydrogel mouse liver hemostasis experiment;

[0074] Figure 43 This is a picture of the chitosan / polydopamine / copper sulfide composite hydrogel mouse liver hemostasis experiment;

[0075] Figure 44 This is the data of the chitosan / polydopamine / copper sulfide composite hydrogel mouse liver hemostasis experiment;

[0076] Figure 45 Schematic diagram of the chitosan / polydopamine / copper sulfide composite hydrogel mouse tail hemostasis experiment;

[0077] Figure 46This is a picture of the hemostasis experiment on the mouse tail using chitosan / polydopamine / copper sulfide composite hydrogel;

[0078] Figure 47 This is the data of the chitosan / polydopamine / copper sulfide composite hydrogel mouse tail hemostasis experiment;

[0079] Figure 48 This is a picture of the mouse heart hemostasis experiment using chitosan / polydopamine / copper sulfide composite hydrogel;

[0080] Figure 49 This is the data of the chitosan / polydopamine / copper sulfide composite hydrogel mouse heart hemostasis experiment. DETAILED DESCRIPTION

[0081] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific examples, but should not be construed as limiting the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the method, steps or conditions of the present invention are within the scope of the present invention. The experimental methods and reagents for which specific conditions are not specified in the examples are all based on conventional conditions or reagents in the art.

[0082] Example 1

[0083] 1. Dopamine (DA) oxidatively polymerizes into polydopamine (PDA)

[0084] (1) Preparation of a pH = 10 sodium hydroxide solution: Weigh 4.0 g of solid sodium hydroxide and dissolve it in deionized water in a beaker. Transfer the solution to a volumetric flask and dilute to 1000 mL to prepare a 0.1 M sodium hydroxide stock solution. Measure the pH of the solution using a pH meter to ensure that it is a sodium hydroxide solution with a pH = 10.

[0085] (2) Construction of the reaction system: Solution A (10 mL of 0.1 M NaOH was added to a fixed volume of 100 mL) was transferred to a clean conical flask and placed on a magnetic stirrer with a stirring speed of 300-500 rpm. Accurately weigh 500 mg of dopamine hydrochloride powder and add it to solution A while stirring continuously to promote the uniform dispersion of dopamine in the alkaline environment. With the addition of dopamine, the oxidative self-polymerization reaction started, and the color of the solution gradually changed from colorless to light brown, dark brown, and finally to black, as shown in the attached figure. Figure 1 During the reaction, the pH value of the solution is monitored in real time using a pH meter. If the pH value deviates from 10, a small amount of sodium hydroxide solution can be added to accurately adjust the pH value so that it is stably maintained at around 10.

[0086] (3) Polymerization reaction: The reaction system was maintained at room temperature and the reaction time was set to 48 hours to allow dopamine to fully undergo oxidative self-polymerization reaction to generate a polydopamine solution.

[0087] (4) Product Dialysis Purification: After the reaction is completed, the generated polydopamine solution is transferred to a dialysis bag with a molecular weight cutoff of 1000-3500 Da. The dialysis bag is placed in a container filled with a large amount of deionized water for dialysis to remove unreacted monomers, by-products, and small molecular impurities such as residual sodium hydroxide. The dialysis fluid is replaced every 12 hours until the conductivity and pH value of the dialysis fluid are basically stable. The entire dialysis process usually lasts for 48 hours.

[0088] (5) Freeze-drying sample preparation: After dialysis is completed, the polydopamine solution in the dialysis bag is transferred to a clean centrifuge tube, and the dialyzed PDA solution is separated by high-speed centrifugation at a speed of 10,000 rpm for 10 minutes. The dialyzed PDA solution is separated by high-speed centrifugation to remove residual small molecule impurities and incompletely polymerized dopamine monomers, and the pure PDA precipitate is placed in a freeze dryer. First, the sample is pre-frozen (-80°C, 4 hours), and then dried for 48 hours under low temperature and low pressure (vacuum 1000hPa, cold trap -77.2°C) to remove moisture from the sample and obtain a pure polydopamine solid product.

[0089] (6) Product analysis: Take an appropriate amount of PDA powder and prepare a 1 mg / mL aqueous solution. Scan the absorption spectrum at 200-800 nm using a UV-visible spectrophotometer. Figure 2 As shown, dopamine (DA) has a maximum absorbance at 280nm, while polydopamine (PDA) absorbs in the 250-800nm ​​band. Compared to DA, its maximum absorption peak is red-shifted (the 280nm absorption peak of DA monomer disappears, while PDA exhibits a broad absorption band from 250-800nm ​​with a maximum absorption peak at 420nm). This is due to changes in the molecular structure and the electron conjugation system during the polymerization process, which causes the absorption peak to shift red. This confirms that dopamine has been successfully oxidized and polymerized into polydopamine.

[0090] 2. Synthesis of CuS NDs by Hydrothermal Method

[0091] (1) Raw material preparation

[0092] Weigh 21 mg of copper chloride dihydrate (CuCl2·2H2O) and 60 mg of polyvinylpyrrolidone (PVP, molecular weight 4000) into a flat-bottomed, high-temperature, and autoclavable reaction vial. Use a pipette to add 5 mL of deionized water to the reaction vial. Place the vial on a magnetic stirrer and stir continuously at 300-500 rpm at room temperature until the solution becomes light blue and transparent.

[0093] (2) Reaction initiation

[0094] Weigh 30 mg of sodium sulfide nonahydrate (Na2S·9H2O) and add it to the light blue solution. As the Na2S·9H2O is added, the color of the solution quickly changes to dark brown, indicating that the reaction has begun.

[0095] (3) Hydrothermal reaction

[0096] The reaction flask was transferred to a 90°C oil bath for a hydrothermal reaction for 30 minutes. After the reaction was complete, the reaction flask was removed from the oil bath and allowed to cool naturally to room temperature. At this point, the solution in the reaction flask was dark green.

[0097] (4) Dialysis treatment

[0098] The dark green solution was transferred to a dialysis bag (molecular weight cut-off 3500Da) and dialyzed against deionized water for 24 hours. The dialysis process effectively removed impurities and small molecules from the solution.

[0099] (5) Centrifugation and purification

[0100] After dialysis, the solution was centrifuged at 13,000 rpm for 20 minutes. After centrifugation, the supernatant was carefully aspirated and filtered through a 0.22 μm filter membrane to remove any remaining large particles.

[0101] (6) Product storage

[0102] After the above treatment, pure and uniformly sized CuS NDs were finally obtained. To ensure their stable performance, the CuS NDs dispersion was purified by dialysis and then freeze-dried (pre-freezing at -80°C for 4 hours and drying at 1000 hPa vacuum for 48 hours) to obtain a solid powder. This ensures the stability of the photothermal material and the accuracy of the subsequent composite hydrogel preparation.

[0103] 3. Preparation of chitosan / polydopamine / copper sulfide multifunctional composite hydrogel. The specific process steps are as follows:

[0104] Step 1: Preparation of polydopamine precursor solution

[0105] Weigh 20.0 mg of freeze-dried polydopamine (PDA) powder and add it to 10 mL of 1% glacial acetic acid solution. Use an ultrasonic cell disruptor (power 200 W, pulse mode: working 2 s / rest 3 s, total time 10 min) to obtain a uniform and stable 2 mg / mL PDA stock solution. Store in the dark at 4°C until use.

[0106] Step 2: Chitosan-polydopamine matrix construction

[0107] Accurately weigh 20.0 mg of chitosan (CS, deacetylation ≥95%) powder and add 1 mL of 1% glacial acetic acid solution containing 2.0 mg of PDA. Stir at 400 rpm on a thermostatic magnetic stirrer (25 ± 1°C) for 2 h until a clear, dark brown homogeneous solution is obtained, indicating that CS and PDA are preassembled through electrostatic interaction.

[0108] Step 3: Preparation of the composite system

[0109] 0.2 mg of copper chloride dihydrate (CuCl2·2H2O) was added to the above solution and stirred evenly. 0.5 mg of the prepared freeze-dried photothermal material copper sulfide (CuS) was weighed and added to the mixed solution to make the final concentration 0.5 mg / mL. Stirring was continued for 15 min until it was completely dissolved to form a Cu-containing 2+ -Composite system of catechol coordination bond and CuS photothermal unit.

[0110] Step 4: Double network cross-linking structure formation

[0111] The system speed was increased to 600 rpm, and 60 μL of 1% glutaraldehyde (GA) solution was added dropwise at a rate of 20 μL / min via a precision syringe pump. GA reacted with the CS amino groups through a Schiff base reaction, simultaneously forming covalent crosslinks with the quinoid structure of PDA, constructing a chemical-ionic dual crosslinking network.

[0112] Step 5: Gelation process control

[0113] 30.0 mg of CS powder was weighed and added into the system three times, with an interval of 5 min each time. The sol-gel transition was observed under stirring at 800 rpm, and the stirring was stopped to obtain a CS / PDA / CuS composite hydrogel with self-supporting ability (see attached). Figure 5 shown).

[0114] The viscosity of the prepared composite hydrogel is shown in Table 1.

[0115] Table 1 Chitosan / polydopamine / copper sulfide composite hydrogel viscometer measurement data

[0116]

[0117] Example 2

[0118] The preparation of chitosan / polydopamine / copper sulfide composite hydrogel was the same as in Example 1, except that the amount of CuS NDs was changed (Step 3: Preparation of composite system: the amount of CuS NDs was 0.75 mg), so that the final concentration was 0.75 mg / ml.

[0119] Example 3

[0120] The preparation of chitosan / polydopamine / copper sulfide composite hydrogel was the same as in Example 1, except that the amount of CuS NDs was changed (Step 3: Preparation of composite system: the amount of CuS NDs was 1 mg) to a final concentration of 1 mg / mL.

[0121] Example 4

[0122] The preparation of chitosan / polydopamine / copper sulfide composite hydrogel was the same as in Example 1, except that the amount of CuS NDs was changed (Step 3: Preparation of composite system: the amount of CuS NDs was 2 mg) to a final concentration of 2 mg / mL.

[0123] Example 5

[0124] The preparation of chitosan / polydopamine / copper sulfide composite hydrogel was the same as in Example 1, except that the mass ratio of chitosan / polydopamine was changed to 1:0.08.

[0125] Example 6

[0126] The preparation of chitosan / polydopamine / copper sulfide composite hydrogel was the same as in Example 1, except that the mass ratio of chitosan / polydopamine was changed to 1:0.1.

[0127] Example 7

[0128] The preparation of chitosan / polydopamine / copper sulfide composite hydrogel was the same as in Example 1, except that the amount of copper chloride dihydrate was changed to 0.1 mg.

[0129] Example 8

[0130] The preparation of chitosan / polydopamine composite hydrogel was the same as in Example 1, except that the amount of copper chloride dihydrate was changed to 0.4 mg.

[0131] Table 2

[0132] Example Chitosan:Polydopamine <![CDATA[Dosage of CuCl2·2H2O]]> Storage modulus (G') 5 1:0.08 Standard amount (0.2 mg) 340Pa 6 1:0.1 Standard amount (0.2 mg) ≥400Pa 7 1:0.1 0.1mg (50% reduction) 200Pa (↓33%) 8 1:0.1 0.4 mg (increase by 100%) 500Pa (↑67%)

[0133] Comparative Example 1

[0134] The preparation of chitosan / polydopamine composite hydrogel is as follows:

[0135] Step 1: The preparation of polydopamine stock solution is the same as in Example 1.

[0136] Step 2: Construction of chitosan-polydopamine mixed system

[0137] Accurately weigh 20.0 mg of chitosan (CS, deacetylation ≥95%) powder and add 1 mL of 1% glacial acetic acid solution containing 2.0 mg of PDA. Stir at 400 rpm on a thermostatic magnetic stirrer (25 ± 1°C) for 2 h until a clear, dark brown homogeneous solution is obtained, indicating that CS and PDA are preassembled through electrostatic interaction.

[0138] Step 3: Ionic cross-linking network formation

[0139] Add 0.2 mg of copper chloride dihydrate (CuCl2·2H2O) to the above solution and continue stirring for 15 minutes until it is completely dissolved. 2+ It forms coordination bonds with the catechol groups of PDA and simultaneously generates ionic crosslinks with the amino groups of CS to construct a double network structure.

[0140] Step 4: Chemical cross-linking

[0141] The system speed was increased to 600 rpm, and 60 μL of 1% glutaraldehyde (GA) solution was added dropwise at a rate of 20 μL / min via a precision syringe pump. GA reacted with the CS amino groups through a Schiff base reaction, simultaneously forming covalent crosslinks with the PDA quinone structure, forming a three-dimensional network gel precursor.

[0142] Step 5: Gelation process control

[0143] Then 30.0 mg of CS powder was weighed and added into the system three times, with an interval of 5 min each time. The sol-gel transition was observed under stirring at 800 rpm, and the stirring was stopped to obtain a CS / PDA composite hydrogel with self-supporting ability (see attached). Figure 4 shown).

[0144] Example 9

[0145] The performance characterization of the chitosan / polydopamine / copper sulfide composite hydrogel prepared in Example 1 was performed using the following specific testing methods:

[0146] 9.1 Rheological properties analysis

[0147] Dynamic shear testing was performed using a rheometer (20 mm diameter): a uniform hydrogel with a diameter of 25 mm and a thickness of 1 mm was prepared, ensuring that there were no bubbles and that the fixture size requirements were met; the test temperature was set at 25°C to simulate the physiological environment.

[0148] ① Amplitude sweep: At a fixed frequency of 1 rad / s, the strain range of 1%-1000% is scanned to determine the linear viscoelastic region.

[0149] ②Frequency sweep: Dynamic modulus test was performed at a frequency range of 0.1-10 Hz under 1% strain.

[0150] ③ Self-repair test: 5 cycles of strain alternation (1%→1500%) were performed to monitor the storage modulus G' recovery rate.

[0151] ④ Shear thinning test: 1-100s -1 The change in apparent viscosity is measured over a range of shear rates.

[0152] As attached Figure 6 、 7 As shown in Figures 9 and 9, a systematic mechanical property analysis of CuS hydrogel (i.e., CS / PDA / CuS hydrogel) and CS hydrogel (i.e., CS / PDA hydrogel) was conducted through rheological tests. The results show that CuS hydrogel exhibits good mechanical stability and fluidity under changes in shear strain, frequency, and shear rate. Especially under high shear strain and high frequency conditions, its structural integrity and mechanical properties are better than CS hydrogel. These characteristics give CuS hydrogel potential advantages in application scenarios that need to withstand large external forces and external forces of different frequencies. At the same time, its shear thinning properties also provide it with the possibility of use in applications that require good fluidity.

[0153] As attached Figure 8 、 10 As shown in the figure, the self-recovery properties of the hydrogel were studied by rheological self-recovery diagrams and self-recovery experimental diagrams. The rheological self-recovery diagram shows that the hydrogel has stable mechanical properties under low strain and can recover the modulus in a short time under high strain, indicating that it has significant self-recovery ability. The self-recovery experimental diagram intuitively shows that the hydrogel can recover its shape (right figure) or structure after undergoing an external incision operation (left figure). These results indicate that hydrogels have potential application value in application scenarios that require self-recovery properties.

[0154] 9.2 Compression mechanical properties

[0155] As attached Figure 11 The figure shows the state of the hydrogel under three different mechanical tests: adhesion, compression, and stretching. The hydrogel showed good adhesion in the adhesion test and was able to firmly adhere to the contact surface, which is important for its application in certain scenarios where adhesion properties are required, such as wound hemostatic dressings.

[0156] Uniaxial compression testing using a universal testing machine:

[0157] Cylindrical gels of equal size were prepared containing different concentrations of CuS NDs (0.5 mg / mL, 1 mg / mL, and 2 mg / mL). The compression rate was set at 1 mm / min until the strain was 80%. Five loading-unloading cycles were performed, and the hysteresis loop area was calculated to evaluate the energy dissipation. Figure 12 As shown in Figure 3, the compression modulus of the hydrogel increased significantly with the increase of CuS NDs content, indicating that the addition of CuS NDs to the hydrogel can enhance its compressive properties.

[0158] 9.3 Injectability and Shape Adaptability Research

[0159] Use medical needle to test the injection performance: Figure 13 As shown, the hydrogel can be freely injected through the needle without clogging and formed into different shapes, which indicates great potential in implant therapy.

[0160] As attached Figure 14 As shown in the figure, after the hydrogel was added to the bottle, the hydrogel began to fill the spaces between the glass beads. This shows that the hydrogel can adapt to the irregular spaces formed by the glass beads, showing the initial characteristics of its shape adaptability. Over time, the hydrogel further filled and wrapped the glass beads, almost completely occupying the spaces between the glass beads. This fully demonstrates that the hydrogel can adapt to the shape of its surrounding environment. No matter how irregular the surrounding space is, the hydrogel can fill and adapt. This shape adaptability is very important for hydrogels in many applications. For example, in the biomedical field, hydrogels can fill and fit according to the shape of the wound, playing a role in protection and promoting healing.

[0161] 9.4 Adhesion performance test

[0162] 9.4.1 Determination of hydrogel viscosity by viscometer

[0163] As attached Figure 15 As shown in Table 1, at 6 rpm, the viscosity of the hydrogel is 92470 mPa.s; at 12 rpm, the viscosity drops to 46338 mPa.s; and at 30 rpm, the viscosity further drops to 18358 mPa.s. At a low speed (6 rpm), the viscosity of the hydrogel is higher, the interaction between the molecular chains is stronger, and the flow resistance is large. As the speed increases (12 rpm and 30 rpm), the molecular chains gradually untie, the flow resistance decreases, and the viscosity decreases. The hydrogel exhibits typical non-Newtonian fluid behavior, and its viscosity changes with changes in shear rate (speed).

[0164] 9.4.2 Adhesion Physical Characterization

[0165] The hydrogel strips stick to the fingers and dynamically adapt to the movements of the fingers, such as Figure 16 As shown, the hydrogel exhibited excellent adhesion and flexibility during the bending of a finger from 180° to 60° and then back to 180°. The hydrogel adhered firmly to the skin at various bending angles and retained its original position and shape even after the finger was straightened. This property holds great potential for broad applications in biomedicine and other fields.

[0166] To evaluate the adhesion performance of the hydrogel in practical applications, the hydrogel was placed on the surface of pig skin. Under the action of force, the hydrogel remained stable without obvious deformation or movement. Figure 17 As shown, it ensures that it can still adhere when subjected to a certain external force.

[0167] Improved test method based on ASTM D3330 standard: The hydrogel adhesion matrix is ​​selected from typical surfaces such as polyisoprene rubber, glass, and plastic. Figure 18 As shown in Figure 19, the hydrogel was able to generate sufficient adhesion between the finger and the bottle cap, successfully sticking the bottle cap to the finger and suspending it in the air, demonstrating its strong adhesion to dry surfaces. In weight testing experiments, the hydrogel exhibited excellent compressive adhesion when subjected to gradually increasing pressure, and was able to withstand loads ranging from 6.86g to 20.70g. These properties indicate that the hydrogel has potential application value in scenarios requiring strong adhesion and compressive adhesion.

[0168] Hydrogel directly adheres to the heart, liver, spleen, lungs and kidneys. Figure 20 As shown, the hydrogel can be seen placed directly on the heart, liver, spleen, lung, and kidney tissues. This image provides a preliminary assessment of the hydrogel's ability to contact and adhere to these tissues. Initially, the hydrogel adhered well to the tissue surface, with no apparent slippage or separation, demonstrating the hydrogel's inherent adhesion.

[0169] Hydrogels can repair sheared tissues by adhesion, such as Figure 21 As shown, hydrogel is used to repair small cuts on the heart, liver, spleen, lung and kidney tissues, with the hydrogel covering the wound. This shows that the hydrogel can fill and cover the wound, forming a certain sealing effect. There are no obvious gaps or hydrogel shedding at the wound in the figure, indicating that the hydrogel can fit the wound to a certain extent. The plasticity of the hydrogel enables it to adapt to the shape of the wound and provide a better fit. Its viscosity helps to pull the edges of the wound together, which may have the effect of stopping bleeding and preventing infection. The hydrogel is biocompatible and does not cause a strong immune response when in contact with tissue, making it suitable for repairing biological tissues.

[0170] 9.5 Characterization of Conductive Properties

[0171] Conductive materials have a significant beneficial effect in the hemostasis process. In organisms, skin damage leads to bleeding, and conductive materials can use their unique electrical properties to positively influence the hemostasis process.

[0172] When the skin is injured and bleeding, an endogenous induced electric field is generated in the wound area, with an electric field strength ranging from 40-200mV / mm. This endogenous electric field has an important physiological stimulating effect on skin cells, promoting their proliferation, migration, and adhesion.

[0173] This experiment aims to evaluate the electrical conductivity of chitosan / polydopamine / copper sulfide composite hydrogel (CS / PDA / CuS). The conductivity was measured using a high-precision digital multimeter.

[0174] Step 1: Sample preparation

[0175] According to experimental requirements, the hydrogel is prepared into a thin sheet to ensure that the sample has a regular geometric shape to facilitate electrode contact and measurement.

[0176] Place the prepared hydrogel sample on an insulating flat surface (such as a glass or plastic plate) to ensure that the sample is stable and does not move.

[0177] Step 2: Electrode Setup

[0178] Place two electrodes on either side of the hydrogel sample, ensuring full contact between the electrodes and the sample. Use a suitable clamp or heavy object to gently press down on the electrodes to ensure good electrical contact between the electrodes and the sample.

[0179] Step 3: Resistance Measurement

[0180] Use a multimeter to measure the resistance of the hydrogel. Connect the red probe to one electrode and the black probe to the other. Turn on the multimeter and select the appropriate resistance range (usually 200kΩ or 2MΩ). Read the resistance value on the multimeter display and write it down. The lower the resistance value, the better the conductivity of the hydrogel.

[0181] Step 4: Record and analyze results

[0182] Record the resistance value of each hydrogel sample and calculate its conductivity. The conductivity (σ) can be calculated using the following formula:

[0183] σ=1 / ρ

[0184] Where ρ is the resistivity, and the calculation formula is:

[0185] ρ=R·A / L

[0186] R is the measured resistance value (Ω);

[0187] A is the cross-sectional area of ​​the electrode in contact with the hydrogel (m 2 );

[0188] L is the distance between the electrodes (m).

[0189] The study investigated the effect of adjusting the amount of CuS added as a photothermal material on the conductivity of the hydrogel. Figure 23As shown in the figure, the conductivity of the experimental group hydrogel (CS / PDA / CuS) was significantly higher than that of the negative control group (CS / PDA). As the CuS content increased from 0.5 to 2 (CS-PDA-CuS 0.5, 0.75, 1, 2), the conductivity increased significantly. The experimental group hydrogel (CS / PDA / CuS) had excellent conductive properties, and the CuS content was positively correlated with the conductivity. The target conductive properties could be achieved by adjusting the CuS ratio.

[0190] 9.6 Antioxidant Activity Evaluation

[0191] Evaluating the antioxidant properties of materials is crucial for their biomedical applications. The DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging assay is a commonly used method for evaluating antioxidant properties. This experiment aimed to evaluate the antioxidant properties of chitosan / polydopamine / copper sulfide composite hydrogels (CS / PDA / CuS) using DPPH free radical scavenging assays.

[0192] Step 1: Preparation of DPPH solution

[0193] Accurately weigh an appropriate amount of DPPH powder, dilute to volume with anhydrous ethanol to prepare a 0.1 mM stock solution, and store in a refrigerator at 4°C away from light.

[0194] Step 2: Hydrogel sample preparation

[0195] Weigh the hydrogel sample, add 2 mL of deionized water, and place in a 5 mL centrifuge tube. Use a tissue homogenizer at an appropriate speed for 3 minutes to obtain a uniform hydrogel solution.

[0196] Step 3: Experimental and control group setup

[0197] Control group: Add 2 mL of DPPH ethanol solution and 2 mL of deionized water into the centrifuge tube and mix well.

[0198] Hydrogel sample group: Add 2 mL of DPPH ethanol solution and 2 mL of hydrogel solution to several centrifuge tubes, respectively. Set up at least 3 parallel samples for each experimental group and mix thoroughly.

[0199] Step 4: Reaction and treatment

[0200] Place all centrifuge tubes in a dark place and react at room temperature for 30 minutes, shaking appropriately during the reaction to ensure uniform mixing. After the reaction is completed, remove undissolved impurities by centrifugation (10000 rpm, 10 minutes) or filtration.

[0201] Step 5: Absorbance measurement

[0202] The absorbance (OD value) of the control group and the hydrogel sample group solutions was measured at a wavelength of 517 nm using a UV-visible spectrophotometer.

[0203] Step 6: Calculate the results

[0204] The DPPH radical scavenging rate was calculated according to the following formula:

[0205] DPPH scavenging(%)=[(A0-A1) / A0]×100%

[0206] A 0 is the absorbance value of the control group (DPPH + ethanol);

[0207] A1 is the absorbance value of the hydrogel sample group (DPPH+ethanol+hydrogel).

[0208] As attached Figure 24 、 25 As shown in Figure 2, the antioxidant properties of the two hydrogels (CS / PDA and CS / PDA / CuS) were evaluated by DPPH scavenging experiments. The bar graph results show that the DPPH scavenging rates of the two hydrogels are similar, both around 80%.

[0209] The above characterization results show that chitosan / polydopamine / copper sulfide composite hydrogel (CS / PDA / CuS) has excellent properties in multiple dimensions. In terms of rheological properties, it has good mechanical stability and fluidity, and strong self-recovery ability. In terms of compressive mechanical properties, the addition of CuS can improve the compressive resistance of the hydrogel. It has injectability and shape adaptability, and has potential in implantation therapy. It has good adhesion properties and exhibits strong adhesion and compressive resistance on different matrices and biological tissues. In terms of conductive properties, the addition of CuS can improve electrical conductivity and help wound hemostasis and healing. In terms of antioxidant properties, CS / PDA and CS / PDA / CuS have similar abilities to scavenge DPPH free radicals.

[0210] Example 10

[0211] To study the photothermal effect of chitosan / polydopamine / copper sulfide composite hydrogel, the photothermal material copper sulfide (CuS NDs) nanoparticles prepared in Example 1 were prepared into sample solutions of different concentrations (0.5 mg / mL, 0.75 mg / mL, 1 mg / mL), irradiated with a 1060 nm near-infrared laser (0.9 W) for 5 minutes, and the surface temperature was recorded using an infrared imager. A core criterion for judging photothermal antibacterial materials is their high efficiency in converting light energy into heat energy, as shown in the attached figure. Figure 26 、 27As shown in Figures 28 and 30, under 1060nm near-infrared (NIR) laser irradiation, at the same concentration, the photothermal effect of the nanoparticles increased with increasing laser intensity, indicating that the photothermal effect of CuS NDs nanoparticles is power-dependent. This demonstrates that temperature regulation of CuS NDs nanoparticles can be achieved by varying laser intensity, providing a precise and facile method for controlling temperature increases by fine-tuning nanoparticle concentration or laser power.

[0212] In order to study the photothermal stability of copper sulfide (CuS NDs) nanoparticles and chitosan / polydopamine / CuS composite hydrogel, the same concentration (1 mg / mL) of copper sulfide (CuS NDs) nanoparticle solution and CS / PDA / CuS composite hydrogel were subjected to laser irradiation (1060 nm, 0.9 W) and natural cooling. Heating and cooling were repeated once for five cycles. The surface temperature was recorded every 30 seconds using an infrared imager. Figure 29 、 30 It can be seen that the heating effects of copper sulfide (CuS NDs) nanoparticles and CS / PDA / CuS composite hydrogel in the five heating-cooling cycles are basically the same, proving that they both have good photothermal stability. Although the encapsulation effect of chitosan slightly reduces the photothermal heating of CuS NDs, the concentration- and power-dependent photothermal behavior of CuS NDs can still be combined to find suitable conditions for subsequent photothermal experiments.

[0213] Example 11

[0214] Antibacterial activity test of chitosan / polydopamine / copper sulfide composite hydrogel prepared in Example 1

[0215] 1. Experimental study on the inhibitory activity of chitosan / polydopamine / copper sulfide composite hydrogel on different bacteria

[0216] 1) Determination of antibacterial activity against Staphylococcus aureus (S. aureus)

[0217] Staphylococcus aureus was cultured in TSB medium and incubated at 37°C and 250 rpm until it reached the logarithmic growth phase. To evaluate the antibacterial activity, 1×10 8 CFU / mL bacterial suspension. 0.1 mL of Staphylococcus aureus was mixed with 0.05 g of chitosan / polydopamine composite hydrogel and 0.05 g of chitosan / polydopamine / copper sulfide composite hydrogel, respectively, and the mixture was stirred under the presence or absence of 1060 nm near-infrared laser (0.9 W / cm 2 ) for 5 min, and then the suspension was further incubated at 37 °C for 10 min, 20 min, 1 h, and 2 h, and then diluted to 2 × 10 4Afterwards, aliquots were plated on solid agar and incubated for 18 h. Colony counts were then performed to quantitatively assess bacterial survival after treatment. Figure 31 As shown in the attached figure, the chitosan / polydopamine / copper sulfide multifunctional composite hydrogel significantly inhibited the viability of Staphylococcus aureus. Figure 32 and attached Figure 33 As shown in the figure, under near-infrared laser irradiation, the antibacterial ability of chitosan / polydopamine / copper sulfide composite hydrogel was significantly enhanced, and the inhibition rate against Staphylococcus aureus exceeded 99%.

[0218] 2) Determination of antibacterial activity against Escherichia coli (E. coli)

[0219] Escherichia coli was cultured in LB medium and incubated at 37°C and 250 rpm until it reached the logarithmic growth phase. To evaluate the antibacterial activity, 1 × 10 8 CFU / mL bacterial suspension. 0.1mL of Escherichia coli was mixed with 0.05g of chitosan / polydopamine composite hydrogel and 0.05g of chitosan / polydopamine / copper sulfide multifunctional composite hydrogel, respectively, and the mixture was stirred under the presence or absence of 1060nm near-infrared laser (0.9W / cm 2 ) for 5 min, and then the suspension was further incubated at 37 °C for 1 h and then diluted to 2 × 10 4 Afterwards, aliquots were plated on solid agar and incubated for 18 h. Colony counts were then performed to quantitatively assess bacterial survival after treatment. Figure 34 、 35 As shown in

[36] , under near-infrared laser irradiation, the antibacterial ability of chitosan / polydopamine / copper sulfide composite hydrogel was significantly enhanced, and the inhibition rate against Escherichia coli exceeded 99%.

[0220] The results of this example confirm that the chitosan / polydopamine / copper sulfide composite hydrogel exhibits higher antibacterial ability, and the enhancement of its photothermal conversion potential further improves its antibacterial ability.

[0221] 2. Experiment on the destruction of biofilm by chitosan / polydopamine / copper sulfide composite hydrogel

[0222] Take 1×10 9CFU / mL of S.aureus and E.coil bacterial liquid was added to a 96-well plate, placed in a 37°C biochemical incubator, and incubated for 48 hours to form a complete biofilm. Thereafter, the biofilm was treated with chitosan / polydopamine / copper sulfide composite hydrogel (with or without 1060nm NIR) and incubated at 37°C for another 20 minutes. Gently remove the incubated sample, discard the upper culture medium, and wash it three times with 10mM PBS. After standing and air-drying, add 100μL of 1% crystal violet and let it stand for staining for 20 minutes. The upper crystal violet was discarded, washed twice with PBS, and after standing and air-drying, add 200μL of 80% ethanol solution, put it on a shaker, and measure the absorbance at 590nm with an enzyme marker. As shown in the attached Figure 37 and attached Figure 38 As shown in the figure, after 20 min of co-incubation, the chitosan / polydopamine / copper sulfide composite hydrogel had a significant destructive effect on the biofilm, effectively eroding the biofilm on the two bacterial strains, and the effect was enhanced after laser irradiation.

[0223] Example 12

[0224] Evaluation of biocompatibility of chitosan / polydopamine / copper sulfide composite hydrogel prepared in Example 1

[0225] ①Hemolysis test

[0226] When the body comes into contact with biomaterials that do not have appropriate blood compatibility, it can lead to undesirable reactions such as red blood cell rupture, thrombosis, and inflammation at the wound site. This phenomenon interferes with the normal wound healing process. Therefore, blood compatibility is crucial for effective wound hemostatic dressings. Studies have reported that a hemolysis rate of <5% represents good blood compatibility. An in vitro hemolytic activity test was used to evaluate the blood compatibility of the CS / PDA / CuS composite hydrogel. The specific experimental steps are as follows:

[0227] 1. Weigh an equal amount of the hydrogel sample to be tested and place it at the bottom of a 5 mL centrifuge tube. Add 2 mL of sterile 1x PBS solution and place the centrifuge tube in a 37°C shaker. Take the hydrogel extract for subsequent experiments.

[0228] 2. Collect an appropriate amount of whole blood from the orbit or heart of a healthy experimental animal (e.g., mouse). Gently mix the collected blood up and down, transfer it to an anticoagulant centrifuge tube, and centrifuge it at 4°C, 2000 rpm for 10-15 minutes. Discard the upper layer of plasma, add an appropriate amount of sterile PBS, gently pipette to mix, and then centrifuge the red blood cells 2-3 times at the same speed until the upper layer solution is clear (no obvious red color) to obtain a pure red blood cell suspension. Finally, dilute the red blood cell suspension with sterile PBS to a desired concentration for later use.

[0229] 3. Prepare several centrifuge tubes and label them as negative control, positive control, and different hydrogel experimental groups. Add 20 μL of red blood cell suspension to each centrifuge tube, then add 1 mL of hydrogel extract and mix. Negative control: Add 1 mL of sterile PBS to the centrifuge tube and mix gently. Positive control: Add 1 mL of distilled water to the centrifuge tube and mix gently to serve as a control for complete hemolysis.

[0230] 4. Place all centrifuge tubes in a 37°C constant temperature incubator and incubate for 1 hour. During this period, gently shake the centrifuge tubes every 15-20 minutes to allow the hydrogel to fully contact and react with the red blood cells.

[0231] 5. After incubation, centrifuge the tube at 1000-2000 rpm for 5-10 minutes to allow the red blood cells to settle at the bottom of the tube. The upper layer of solution is the supernatant after hemolysis.

[0232] 6. Carefully aspirate the supernatant from each centrifuge tube and transfer it to a new, clean centrifuge tube. Measure the absorbance (OD) of each supernatant at 540 nm using a spectrophotometer.

[0233] According to the measured absorbance value, the hemolysis rate (%) was calculated according to the following formula:

[0234] Hemolysis rate (%) = (OD value of experimental group - OD value of negative control group) / (OD value of positive control group - OD value of negative control group) × 100%

[0235] It is generally believed that a hemolysis rate of less than 5% indicates no hemolysis; a hemolysis rate between 5% and 10% indicates mild hemolysis; and a hemolysis rate greater than 10% indicates obvious hemolysis.

[0236] As attached Figure 39As shown, the supernatant was collected for quantitative analysis and it was found that the hemolysis ratio of the hydrogels in different experimental groups was <5%, showing good blood compatibility. Overall, the CS / PDA / CuS composite hydrogel showed good blood compatibility. Traditional hemostatic materials cause red blood cell rupture due to physical friction or chemical stimulation, and have a medium to high risk of hemolysis; precious metal photothermal materials damage red blood cells due to the surface charge of nanoparticles or metal ion toxicity, and have a high risk of hemolysis; synthetic polymer gels stimulate red blood cells due to cross-linker residues or degradation products, and have a medium risk of hemolysis. Composite hydrogels achieve efficient hemostasis and antibacterial functions while significantly reducing the risk of hemolysis, ensuring excellent blood compatibility (hemolysis rate <5%), and showing blood compatibility that is superior to traditional materials and precious metal systems. They are suitable for clinical scenarios with high safety requirements, especially for complex wounds that require direct contact with blood (such as deep tissue hemostasis and in vivo trauma repair), achieving a synergistic balance between function and safety.

[0237] ② Coagulation test

[0238] Coagulation performance is a key indicator in wound hemostatic dressing research. Good coagulation performance can effectively promote wound hemostasis and accelerate wound healing. In vitro coagulation experiments were conducted to examine the coagulation performance of the CS / PDA / CuS composite hydrogel, providing experimental evidence for its application in wound hemostatic dressings.

[0239] The specific experimental steps are as follows:

[0240] 1. Collect whole blood from the eye sockets of healthy mice and place the blood into an anticoagulant tube containing sodium citrate solution. Gently invert the anticoagulant tube several times to thoroughly mix the blood and sodium citrate solution to prevent blood coagulation.

[0241] 2. Blood decalcification: Place the anticoagulant tube containing whole blood in a centrifuge at 3000 rpm for 10 minutes. After centrifugation, carefully aspirate the upper plasma layer into a new tube. Add an appropriate amount of sodium citrate solution to the new tube and gently invert to mix thoroughly to ensure that the calcium ions in the plasma are fully chelated and the blood is fully decalcified.

[0242] 3. Blood Recalcification: Take an appropriate amount of decalcified plasma, add CaCl2 solution, and gently mix to restore the calcium ion concentration in the plasma to physiological levels, thereby restoring the blood's coagulation ability. During the recalcification process, pay attention to the amount of CaCl2 solution added to ensure that the final calcium ion concentration accurately reaches the physiological level.

[0243] 4. Weigh the CS / PDA / CuS composite hydrogel and place it in the corresponding wells of a 96-well plate, ensuring that the hydrogel is in full contact with the well bottom and evenly distributed. Then, use a pipette to slowly add 1 mL of calcium-recalcified blood to each well, ensuring that the blood completely covers the surface of the hydrogel. Gently shake the 96-well plate to thoroughly mix the hydrogel and blood. Let it stand at room temperature for 5-10 minutes to allow the hydrogel and blood to fully react.

[0244] 5. After the reaction is complete, add 5 mL of sterile water to each well and gently shake the 96-well plate to allow the uncoagulated blood to fully combine with the water, disrupting the remaining coagulation reaction system and terminating the coagulation process. Carefully transfer the solution in the 96-well plate to a centrifuge tube. Place the centrifuge tube in a centrifuge and centrifuge at 3000 rpm for 10 minutes. After centrifugation, carefully aspirate the supernatant and transfer it to a new, clean centrifuge tube for subsequent absorbance measurement.

[0245] 6. Place the supernatant liquid in a spectrophotometer and measure its absorbance (OD value) at a wavelength of 540 nm.

[0246] According to the measured absorbance value, the blood coagulation index (BCI) was calculated according to the following formula:

[0247] BCI=OD sample / OD control×100%

[0248] OD sample is the absorbance value of the supernatant of the experimental group (hydrogel experimental group), and OD control is the absorbance value of the supernatant of the negative control group.

[0249] The coagulation performance of the hydrogel was judged according to the blood coagulation index (BCI) value:

[0250] The BCI value is close to 100%, indicating that the blood basically does not coagulate after adding the hydrogel, that is, the hydrogel has no obvious coagulation effect;

[0251] The BCI value is between 50% and 100%, indicating that the hydrogel has a certain coagulation effect, but the coagulation effect is general;

[0252] The BCI value is less than 50%, indicating that the hydrogel has good coagulation properties and can effectively promote blood coagulation.

[0253] As attached Figure 40 、 41As shown in the figure, by measuring and analyzing the coagulation index of the hydrogels in different experimental groups, it was found that the coagulation index of the CS / PDA / CuS composite hydrogel experimental group was significantly lower than that of the negative control group and similar to that of the positive control group, indicating that the composite hydrogel has good coagulation properties. This may be because certain components in the CS / PDA / CuS composite hydrogel can interact with coagulation factors in the blood, activating the coagulation pathway and promoting blood coagulation. In addition, the three-dimensional network structure of the hydrogel may also provide a suitable microenvironment for the coagulation reaction, promoting platelet aggregation and thrombin generation.

[0254] In summary, CS / PDA / CuS composite hydrogel has good application prospects in the field of wound hemostatic dressing.

[0255] ③Hemostasis experiment

[0256] The mice were randomly divided into an experimental group (using hydrogel to stop bleeding) and a control group (using conventional compression to stop bleeding without using hydrogel to stop bleeding).

[0257] Liver hemostasis test

[0258] The skin was cut along the midline of the mouse abdomen, and the abdominal muscles were bluntly separated to expose the liver. A 1 cm wound was made on the surface of the liver using a scalpel to allow the liver to bleed continuously. An appropriate amount of hydrogel sample was evenly applied or covered on the liver wound of the experimental group mice, and gently pressed to make it fit tightly with the wound; the control group mice used conventional compression hemostasis methods. The amount of liver bleeding in the experimental and control group mice was recorded separately. Each experimental and control group contained at least 3 mice, and the average value was taken as the bleeding amount data of the group. As shown in the attached figure. Figure 43 and attached Figure 44 As shown in the figure, the amount of bleeding in the experimental group was significantly less than that in the control group, indicating that the hydrogel has a good hemostatic effect.

[0259] Tail hemostasis assay

[0260] Use a scalpel to make a cut on the mouse tail at about 50% of the distance from the tail tip, so that the mouse tail continues to bleed. The mice in the experimental group immediately apply or stick an appropriate amount of hydrogel sample to the wound and gently press it to make it fully contact with the wound; the mice in the control group use conventional compression hemostasis method. The amount of bleeding of the experimental and control group mice is recorded separately. Each experimental and control group contains at least 3 mice, and the average value is taken as the bleeding amount data of the group. As shown in the attached Figure 46 and attached Figure 47 As shown in the figure, the amount of bleeding in the experimental group was significantly less than that in the control group, indicating that the hydrogel has a good hemostatic effect.

[0261] Cardiac hemostasis experiment

[0262] The heart was exposed by opening the thorax between the ribs of the mouse. A syringe needle was used to puncture the left ventricular wall to create a cardiac bleeding model. The mice in the experimental group were immediately smeared or injected with an appropriate amount of hydrogel sample at the cardiac puncture site to cover the bleeding site; the mice in the control group were given conventional compression hemostasis methods. The amount of cardiac bleeding in the experimental and control groups was recorded separately. Each experimental and control group contained at least 3 mice, and the average value was taken as the bleeding amount data of the group. Figure 48 and attached Figure 49 As shown in the figure, the amount of bleeding in the experimental groups of hydrogels was compared with that in the control group. The experimental groups had significantly less bleeding than the control group. The chitosan / polydopamine composite hydrogel had obvious shedding, while the chitosan / polydopamine / copper sulfide composite hydrogel could still adhere to the damaged tissue, thereby significantly reducing the amount of bleeding, indicating that the chitosan / polydopamine / copper sulfide composite hydrogel had a good hemostatic effect.

[0263] Control Example 2: Control experiment with missing chitosan (CS)

[0264] Sample composition: polydopamine (PDA) + copper sulfide nanoparticles (CuS NDs)

[0265] Preparation of PDA stock solution: Dissolve 20 mg of PDA powder in 10 mL of 1% glacial acetic acid solution and sonicate until homogeneous.

[0266] Composite system construction: Take 1 mL of PDA solution (containing 2 mg of PDA), add 0.2 mg of CuCl2·2H2O and 0.5 mg of CuSNDs, and stir to form a mixed solution.

[0267] Chemical cross-linking: 60 μL of 1% glutaraldehyde solution was added dropwise to initiate the Schiff base reaction and construct a three-dimensional network.

[0268] Gelation control: add 30 mg of PDA powder and stir until a self-supporting hydrogel is formed.

[0269] Control Example 3: Control experiment with lack of polydopamine (PDA)

[0270] Sample composition: chitosan (CS) + copper sulfide nanoparticles (CuS NDs)

[0271] Experimental steps:

[0272] Preparation of chitosan solution: Dissolve 20 mg of chitosan in 1 mL of 1% glacial acetic acid solution and stir until clear.

[0273] Composite system construction: 0.2 mg CuCl2·2H2O and 0.5 mg CuS NDs were added and Cu 2+ Cross-linked with chitosan amino groups (lacking PDA catechol coordination bonds).

[0274] Chemical cross-linking: 60 μL of 1% glutaraldehyde solution was added dropwise to form a gel precursor (only relying on chitosan-glutaraldehyde cross-linking, with poor adhesion).

[0275] Gelation control: add 30 mg chitosan and stir until gel is formed.

[0276]

Claims

1. A chitosan / polydopamine / copper sulfide composite hydrogel, characterized in that: The composite hydrogel is prepared by dynamically cross-linking chitosan, polydopamine and copper sulfide nanoparticles in a mass ratio of 1:0.04-0.1:0.01-0.04, and has a three-dimensional network structure.

2. The composite hydrogel according to claim 1, characterized in that The preparation method of polydopamine comprises the following steps: dissolving dopamine hydrochloride in a NaOH aqueous solution with a pH of 9-11 and a concentration of 0.1-0.2M, stirring at room temperature for 24-48 hours, dialyzing for 48 hours, and then freeze-drying to obtain polydopamine PDA powder.

3. The composite hydrogel according to claim 1, characterized in that The preparation method of the copper sulfide nanoparticles comprises: dissolving CuCl2·2H2O and polyvinyl pyrrolidone in deionized water at a mass ratio of 7:20, adding Na2S·9H2O, reacting at 80-90°C for 15-45 minutes, and obtaining a copper sulfide nanoparticle CuS NDs dispersion after purification by dialysis.

4. A method for preparing the composite hydrogel according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Preparation of polydopamine stock solution: PDA powder was dissolved in 1% glacial acetic acid solution and sonicated to obtain a PDA solution with a concentration of 2-5 mg / mL; (2) Chitosan-polydopamine pre-assembly: dissolving chitosan in the PDA solution of step (1) and stirring to form a homogeneous system; (3) Multi-component cross-linking: CuCl2·2H2O and CuS NDs were added to the homogeneous system in step (2). 2+ -Catechol coordination bond and chitosan amino ion cross-linking form a composite system; (4) Chemical cross-linking strengthening: adding 1-2% glutaraldehyde solution to the composite system of step (3) to initiate a Schiff base reaction and construct a three-dimensional network gel precursor; (5) Gelation control: Add chitosan powder and stir until a composite hydrogel is formed.

5. The preparation method according to claim 4, characterized in that In step (2), the amount of chitosan added is 40% of the total mass of chitosan.

6. The preparation method according to claim 4, characterized in that In step (3), the mass ratio of CuCl2·2H2O to CuS NDs is 1:2.5-10.

7. The preparation method according to claim 4, characterized in that In step (4), the amount of glutaraldehyde solution added is 60 μL, the droplet acceleration rate is 1-2 drops / second, and the stirring time is 30-60 minutes.

8. An application of the composite hydrogel according to claim 1, characterized in that: The composite hydrogel is used for preparing hemostatic dressings, antibacterial materials or biomedical engineering materials.

9. The use of the composite hydrogel according to claim 8, characterized in that: Hemostatic dressings are hemostatic materials used for surface wounds, deep tissue and organ bleeding.